The Management of Tahfidz Al-Qur'an Learning at Homeschooling Public Learning Center - Raudhah Saragih; Mesiono Mesiono; Inom Nasution (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2021)
This article aims to determine and analyze the Tahfidz Al-Qur'an Learning Management at Homeschooling Public Learning Center of Abi And Ummi Junior High School Level of Islamic Education Foundation Jannati Medan Helvetia, which includes planning, organizing, implementing, and evaluating. Researchers are interested in knowing more about the management of tahfidz Al-Qur'an learning in this school because in its application this school is homeschool-based with the target of tahsin reading the Qur'an in conjunction and using STIFIn as a learning aid. This article uses a case study approach and uses three sources of evidence to be the focus of data collection in this study, namely: direct observation, interviews, and documentation. Data analysis in this study is in the form of making a detailed description of the case. In data analysis, the researcher reduces the data by summarizing, choosing the main things, focusing on the important things, looking for themes and patterns, and removing unnecessary ones, so that the reduced data provides a clearer picture. Then the researcher displays the data (presents the data) to make it easier to understand what is happening. Furthermore, the researcher carried out a conclusion drawing (concluding drawing/verification). The result of this article indicates that the planning of tahfidz Al-Qur'an learning is in the form of recruitment of supervising teachers, standards in new student admissions, preparation of learning programs, and setting memorization targets as a form of optimizing the homeschooling base where schools are expected to be able to create a comfortable and enjoyable learning and tahfidz atmosphere. so that it can give birth to Hafizh Al-Qur'an with the quality of reading Quran well. Organizing tahfidz Al-Qur'an learning using STIFIn as a tool to identify student intelligence machines to direct students to recognize appropriate memorization methods and teachers can take a personal approach to students so that students feel comfortable while memorizing the Qur'an and grow a love of Al-Qur'an -Qur'an. The implementation of tahfidz Al-Qur'an learning is in the form of face-to-face small groups where one supervising teacher is responsible for 8-10 students. The schedule for implementing the tahfidz Al-Qur'an learning is prepared by the tahfidz coaches, school principals and supervising teachers. There are 6 hours in a daily special time provided for tahfizh learning which is divided into 3 meetings, the first 1 hour to increase memorization, the second 3 hours to repeat memorization and the third 2 hours to increase memorization. Evaluation of tahfidz Al-Qur'an learning that is applied in the form of evaluations per day, month, and semester.